Growth of Candida albicans colony on heat cured acrylic plat in inclusion of lime fruit extract (Citrus aurantifolia) 40% as desinfectant: Pertumbuhan koloni Candida albicans pada plat akrilik heat cured dalam perendaman ekstrak kulit buah jeruk nipis (Citrus aurantifolia) 40% sebagai desinfektan - Kadek Dwi Dessy Sapitri (Makassar Dental Journal, 2022)
Heat cured acrylic (HCA) resin has a rough, hard and porous surface. This causes food scraps to stick frequently and makes it easier for Candida albicans to grow. Lime peel extract (citrus aurantifolia) is a natural ingredient that is antifungal. The pur-pose of this study was to determine the growth of C.albicanscolonies on heat cured acrylic dentures in 40% immersion of lime peel extract. The HCA resin plate samples were 40 samples, namely the 40% lime peel extractconcentration group, the negative control group (akuades) and the positive control group which were soaked for 2 hours and 6 hours. The design of this study was a post-test only control group with data analysis using the one-way Anova test. The results showed that each group was normally distributed and the variance data was heterogeneous (p>0.05). It is concluded that 40% lime peel extract can inhibit the growth of C.albicans colonies on HCA resin plates.